Dari Risiko Menjadi Peluang: Analisis Strategi Ketahanan Keuangan PT Denpoo Mandiri Indonesia Dalam Menghadapi Perekonomian Global - Angelina Wijaya Tan; Nathalie Elshaday Betrix Ambouw; Shirky Kharisma Fitri Hasnita; Maria Yovita R.Pandin (CEMERLANG : Jurnal Manajemen dan Ekonomi Bisnis, 2024)
The ever-changing and volatile global economy poses significant challenges for businesses around the world. Faced with this uncertainty, financial resilience strategies are essential to help businesses not only survive but also thrive in a turbulent environment . This article aims to analyze the financial recovery strategies undertaken by PT. Denpoo Mandiri Indonesia in the face of a volatile global economy. Through a case study approach, we explore the specific steps these companies took to turn risks into opportunities, as well as the strategies that proved most effective in strengthening their key financial positions. Taking into account factors such as portfolio diversification, risk management and financial flexibility, we present an in-depth look at how PT Denpoo Mandiri Indonesia has managed to overcome the challenges of the global economy and turn them into opportunities for growth and long-term success.